Wildlife Protection and Habitat Management Practice and Perspectives - Beltrán, Juan F.; Abellán, Pedro; Litvaitis, John (2022)
The management of wildlife populations and their habitats are interdisciplinary fields that encompass many scientific disciplines that also impact the lives of people. Therefore, these are truly applied sciences where human dimensions play an important role.This book highlights the importance of conducting rigorous studies to design and implement the effective management and restoration of wild populations and their habitats. A new paradigm in conservation is developing that goes beyond the boundaries of protected areas to achieve the goal of sustainable development. The 16 papers in this book, including reviews and a project report, cover a broad range of topics, exploring a diversity of subjects that are representative of current practices and novel applications.We would like to thank both the MDPI publishers and editorial staff for their support and help during the process of editing this book, in addition to the authors for their contributions.